TOURISM ECONOMIC IMPACT OF SOUTH LAMPUNG REGENCY - Cahyadi, Hery Sigit (Journal of Indonesian Tourism, Hospitality and Recreation)
ABSTRACT                                                       South Lampung regency as one of the gates of Sumatra Island became one of the many tourist destinations in Indonesia, especially on the island of Sumatra. The existence of tourism activities in South Lampung District economic impacts for the community, such as increasing public income, increased employment and business opportunities for local communities. The purpose of this research is to measure the economic impact of tourism activities in South Lampung Regency. In analyzing the economic impacts of tourism activities in South Lampung District using Keynesian Income Multiplier and multiplier analysis to see the direct impact, indirect impacts, and further impacts. Based on the results of the analysis shows that the presence of tourism activities in South Lampung Regency has had an economic impact on the local economy even though the perceived impact is still small. As evidenced by the value of Keynesian Income Multiplier is 1.95, value ratio Income Multiplier of Type I 1.09, and value ratio Income Multiplier of Type II 1.34. Keywords: South Lampung Regency, Economic Impact, Tourism Activities, Multiplier Effects